Let x 1 and x 2 be the roots of the equation x 2 − 3 x + 1 = 0 . The value of:
x 2 x 1 + x 1 x 2 can be written as a b where a and b are coprime positive integers.What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Guilherme, here is another solution for those who are not familiar with some of your methods:
If we square the given expression,we will obtain:
( x 2 x 1 + x 1 x 2 ) 2 = x 2 x 1 2 + x 1 x 2 2 + x 1 x 2 2 x 1 x 2 = x 1 x 2 x 1 3 + x 2 3 + x 1 x 2 2 x 1 x 2 .Observe:
x 1 3 + x 2 3 = ( x 1 + x 2 ) 3 − 3 x 1 x 2 ( x 1 + x 2 ) .From vietas formulas we have :
x 1 + x 2 = 3 ( 1 )
x 1 x 2 = 1 ( 2 )
Therefore x 1 3 + x 2 3 = 1 8 and the expression is equal to :
1 1 8 + 1 2 ∗ 1 and by making the operations we obtain :
( x 2 x 1 + x 1 x 2 ) 2 = 2 0 where :
x 2 x 1 + x 1 x 2 = 2 0 = 2 5 .Thus, a = 2 and b = 5 and a + b = 7
Log in to reply
Way better than my solution. I got the easy job because the roots are powers oh φ .
Guilherme ,what if we had a similar problem to this one but with different equation ,would you still be able to use the Golden Ratio identity ?
Log in to reply
I would not. This only works because x 1 and x 2 are powers of φ , where φ 2 = φ + 1 .
Problem Loading...
Note Loading...
Set Loading...
x 2 − 3 x + 1 = 0 , x 1 ≥ x 2 Bhaskara’s Formula x 1 = 2 3 + 5 x 2 = 2 3 − 5 Golden Ratio Identity x 1 = 2 5 + 1 x 2 = 2 5 − 1 a b = x 2 x 1 + x 1 x 2 ⇒ a b x 1 x 2 ( x 1 − x 1 x 2 + x 2 ) ( x 1 + x 2 ) Vieta’s Formulae a b = 1 ( 3 − 1 ) 5 a b = 2 5 a + b = 7 .